The Influence of Behavioral Biases on Individual Taxpayer Compliance Decisions in Indonesia - Judijanto, Loso; Mooduto, William Indra S.; Ambarwati, Retnoning; Herlambang, Albert (Eastasouth Institute, 2025)
This study investigates the influence of behavioral bias and financial literacy on tax compliance decisions among individual taxpayers in Indonesia. Using a quantitative approach, data were collected from 250 respondents through a structured questionnaire using a Likert scale (1–5). The analysis was conducted using SPSS version 25, with validity, reliability, and classical assumption tests confirming the robustness of the data. Multiple linear regression analysis revealed that behavioral bias has a negative and significant effect on tax compliance, indicating that cognitive distortions—such as overconfidence, loss aversion, and mental accounting—reduce the likelihood of compliance. Conversely, financial literacy has a positive and significant influence, suggesting that financially literate individuals are more likely to understand tax obligations and comply voluntarily. The regression model explains 43.2% of the variance in tax compliance decisions. These findings underscore the importance of addressing psychological barriers and enhancing taxpayer education to improve voluntary compliance in Indonesia.